Mesozoic Notocupes revealed as the sister group of Cupedidae (Coleoptera: Archostemata) - Li, Yan-Da; Tihelka, Erik; Yamamoto, Shûhei; Newton, Alfred F.; Xia, Fang-Yuan; Liu, Ye; Huang, Di-Ying; Cai, Chen-Yang (Frontiers in Ecology and Evolution, 2023)
Despite encompassing only about 50 extant species, beetles of the suborder Archostemata have a rich fossil history, being known from the Permian and dominating coleopteran assemblages in the Mesozoic before declining in richness towards the Late Cretaceous. Given the limited diversity of extant archostematans, fossils provide a valuable line of evidence for reconstructing the relationships among its constituent families. Here we re-evaluate the phylogenetic position of the Triassic-Cretaceous genus Notocupes, the most species-rich archostematan taxon in the fossil record. Exquisitely preserved fossils from the Middle Jurassic Haifanggou Formation (Daohugou; ~165 Ma) and mid-Cretaceous amber (~99 Ma) reveal critical differences from Ommatidae in the presence of separated procoxae and overlapping abdominal ventrites. Our analyses confirm Notocupes is not a member of Ommatidae, but is closely related to Cupedidae. Our fossils reveal that Notocupes possessed unique adaptations for protecting their appendages, such as unusual dorsal pronotal grooves for the reception of antennae and epipleural grooves for the reception of legs, shedding light on ecological interactions in Mesozoic saproxylic habitats. The high similarity between Jurassic and Cretaceous Notocupes provides an exceptional example of long-term morphological stasis, suggesting a consistent microhabitat for the group.